The Role of Workload and Work Discipline in Improving Job Satisfaction and Performance of Outsourcing Employees (International Journal of Scientific Research and Management (IJSRM), 2019)
This study examines how to improve outsourcing employees’ performance through workload and work discipline using job satisfaction as intervening variable. As many as 43 outsourcing workers at PT Bank Rakyat Indonesia Jember are involved as samples. The sampling techniques used is census because it uses entire population as samples. This study used quantitative data through the distribution of questionnaires. Path analysis is performed for the purpose of this study. The results exhibit significant direct negative impact of workload on employee’s job satisfaction and performance, significant direct positive impact of work discipline on employee’s job satisfaction and performance, and significant direct positive and significant effect of job satisfaction on employees’ performance. The results also found significant indirect effects of workload and discipline on employee performance with job satisfaction as intervening variable but the magnitude is weaker than its direct effect.